Peradilan In Absentia sebagai Upaya Pengembalian Aset Milik Negara dalam Tindak Pidana Korupsi - Suryadi (Faculty of Law Hang Tuah University, 2020)
The In Absentia trial is regulated in Article 38 number 1 of Law Number 31 of 1999 as amended to Law Number 20 of 2001 concerning Eradication of Corruption. The handling of corruption cases sometimes has obstacles in the disclosure of cases, bearing in mind that not a few cases are not revealed and the perpetrators cannot be brought before the court. The purpose of this research is to find out the judiciary in absentia as an effort to recover state assets in corruption. The type of research used is normative legal research. The results showed that theoretically the trial in absentia gave birth to two different views, allowing for the achievement of the legal substance and prohibiting for reasons of violating human rights. However, in the case of the implementation of the trial in absentia, it can be done so as not to violate the defendant's human rights, if the formal requirements have been met. The eradication of corruption does not only talk about the handling or examination of the defendant in front of the trial, but the state through law enforcement tools to save or restore state financial losses through mechanisms both criminal and civil.